Opportunity principle in criminal procedural action and restorative justice (2023)
Contemporary criminal procedural systems, which tend to be accusatory, often establish a regime for criminal action that includes the so-called “opportunity principle”, which grants the holder of criminal action a margin of discretion that allows them to abstain from exercising such action, definitively or temporarily, in legally established cases. The current Colombian criminal procedural system regulates the “opportunity principle”, linking its exercise to various criteria, which are more oriented towards the conception of criminal action as a state duty rather than a focus on the rights of victims of criminal conduct. This work proposes a divergent approach, aimed at establishing the foundations of a conception of the opportunity principle in criminal procedural action that gives more relevance to restorative justice than to retributive justice, in the construction of doctrine on the opportunity of criminal procedural action and, therefore, more projection to the perspective of victims’ rights than to the perspective based on the right or power of the State to punish and the consequent duty to exercise such action.